The impact of solar energy investment in multilateral development banks on technological innovation: Evidence from a multi-period DID method - Sun, Weijia; Li, Ruotong; Cai, Renjie; Ji, Zheyan; Cheng, Mingshuang (Frontiers in Energy Research, 2023)
Solar energy technology innovation plays a crucial role in achieving green and sustainable development and a low-carbon economy. The literature focuses on the economic and environmental effects of solar energy but ignores the role of solar energy investment in multilateral development banks (MDBs) on technological innovation. Using the panel data of 37 countries, including OECD countries and China, from 2006 to 2019, we adopt a multi-period DID model to empirically analyze the impact of solar energy investment in MDBs on technological innovation. The results show that solar energy investment in MDBs can significantly promote technological innovation, with the conclusion still being valid after conducting a series of robustness tests. The heterogeneity results indicate that the promoting effect of solar energy investment in MDBs on technological innovation is more significant in regions with higher human capital and higher innovation ability. The findings of this paper can be a useful addition to the literature on solar energy and technological innovation and serve as a useful reference for countries around the world as they accelerate solar energy investment and promote technological innovation.